TAUSIYAH PENDAKWAH DI YOUTUBE MENGENAI NIKAH SIRRI: INTERPRETASI DAN PENGAITAN HUKUM - Kholifatun Nur Mustofa (Indonesian Journal of Shariah and Justice, 2021)
Youtube is one of the means to spread preaching tausiyah; through Youtube, people can access tausiyah anytime and anywhere. One of the discussions offered was a lecture delivered by Mamah Dedeh and Ustadz Abdul Somad (UAS) about sirri marriage. The author uses the two preachers to focus the discussion and theme. First, the author uses YouTube as a research source. Then this paper focuses on discussing how the preacher interprets the sirri marriage. Do tausiyah Mamah Dedeh and UAS convey sirri marriage by linking Islamic law and state law? The results of the author's search, Mamah Dedeh understands that the context of sirri marriages being carried out today is different from the sirri marriages applied by the prophet, sirri marriages carried out by the community today are marriages that are carried out secretly, even the conditions of marriage are not all fulfilled. So the marriage is invalid because it does not meet the requirements. Regarding the delivery of a lecture linking state law and Islamic law, Mamah Dedeh was firm in conveying that a marriage that meets the pillars and conditions is not enough. He emphasized that in Indonesia, there are regulations regarding the registration of marriages that protect women. Meanwhile, UAS does not link state law and Islamic law. UAS advises not to do unregistered marriages because there are many harmful effects for women.